2012
DOI: 10.3892/ijmm.2012.1178
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition and apoptosis-inducing effect on human cancer cells by RCE-4, a spirostanol saponin derivative from natural medicines

Abstract: Reineckia carnea has been used to treat several diseases in folk remedies. RCE-4 has been isolated from several plants of the family Liliaceae, but its biological activity has not yet been reported. In the present study, we found that RCE-4 exhibited potent cytotoxicity to the tested human cancer cell lines, and the CaSki cell line was the most sensitive with an IC50 of 3.37 µM. Thus, we presented the apoptosis-inducing effect of RCE-4 on CaSki cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Steroidal glycosides and triterpenes, commonly known as saponins are a group of compounds abundant in plants and have been reported to be cytotoxic to cancer cells of different origins141516. Degalactotigonin, uttroside A and uttroside B are the cytotoxic saponins isolated from S. nigrum Linn89, which is a widely used herb in the Indian traditional systems of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Steroidal glycosides and triterpenes, commonly known as saponins are a group of compounds abundant in plants and have been reported to be cytotoxic to cancer cells of different origins141516. Degalactotigonin, uttroside A and uttroside B are the cytotoxic saponins isolated from S. nigrum Linn89, which is a widely used herb in the Indian traditional systems of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…RCE-4 isolated from Reineckia carnea has been found to exhibit potent cytotoxicity on yet another cervical cancer cells CaSki (Wang et al, 2013). In this investigation, the IC 50 was found to be 3.37 µM.…”
Section: Rce-4mentioning
confidence: 66%
“…The other cervical cancer cell lines where plant extracts or its derivatives have been found effective are KB3-1 (Staerk et al, 2002;Kaewpiboon et al, 2012), SiHa Gupta eta al., 2013), C33a (Lee et al, 2012) and CaSki (Wang et al, 2013).…”
Section: Mechanismsmentioning
confidence: 98%
“…In previous studies, RCE-4, as a potential anti-cervical cancer chemotherapy drug, was demonstrated to induce mitochondria-mediated apoptosis, which was considered to be the mechanism for inhibiting the proliferation of CaSki and HeLa cells (5,9). The aim of the present study was to clarify whether RCE-4-induced autophagy is a survival or death mechanism during cervical cancer treatment.…”
Section: Introductionmentioning
confidence: 89%
“…To the best of our knowledge, the steroidal saponins primarily exert anti-inflammatory and antitumor activity, with toxicity towards both normal and tumor cells (7). However, RCE-4 exhibited a significant anti-inflammatory (8) and notable cytotoxic effects on cancer CaSki, HeLa, HT-29 and CNE-2 cell lines, whereas it exerted relatively weak cytotoxic effects in normal Marc-145 and MDCK cells (9). Furthermore, CaSki cell xenograft experiments using nude mice demonstrated that RCE-4 inhibited tumor growth and had notably low levels of toxicity in normal tissues, including those of the liver and the uterus (10).…”
Section: Introductionmentioning
confidence: 99%